Władza dyskrecjonalna administracji publicznej a sytuacja prawna jednostki – kilka refleksji - Duniewska, Zofia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
This paper concerns discretionary power of the public administration and its influence on the legal situation of individuals. The power, important for those governing and even more important for those who encounter its results, has aroused doubts and disputes for a long time. Application of this power is determined by various factors. First of all, it is determined by law; it requires legal grounds and must be in its limits. The discretionary power assumes various forms. Its expression is seen in many spheres of activity (sometimes passivity) of the public administration. Based on good law, proper use of this power may aid those governing, a human being and the society. Bad law and its misuse undermines respect of the entities appointed to act in the public capacity. What is more, it endangers the welfare of people who should be supported and protected by the authority bodies which honestly and reliably take care of welfare of individuals and communities created by them.
Keywords: individual; discretionary power; discretionary entitlements; community; public administration